Vulnerability methodology and dataset for credit scoring and financing in Ecuador and Guatemala - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
We have created a methodology and produced datasets of climate risk vulnerability (i.e. droughts, floodings, storms, frozen) integrated in a refinancing model in Guatemala powered by YAPU for Genesis Empresarial Foundation. The model is being expanded to other countries (e.g., Ecuador).